EFEKTIVITAS METODE KOOPERATIF GROUP INVESTIGATION DALAM PENINGKATAN KUALITAS PROSES PEMBELAJARAN - Yulianto, Agung (Fakultas Ekonomi, Universitas Negeri Semarang, 2010)
The objectives of this study are: (1) to know the effectiveness of Group Investigation method to improve the quality of studentsâ motivation in Budgeting subject, and (2) to know the effectiveness of Group Investigation method to improve the quality ofÂ studentsâ learning in Budgeting subject.Â This study was Class-Action Research which was designed into two main cycles, the 1st cycle and the 2nd cycle. Each cycle consisted of some stages; they were planning - implementation - evaluation and reflection. The research was conducted at accounting class, Economics Faculty, UNNES started on June until November 2008. The collected data were: (1) students activities during learning, (2) faculty and student interaction, (3) the level of student motivation, (4) student achievement and (5) students response to the learning process. Observation of the learning process carried out by two lecturers. The quality of the learning process in the classroom can be illustrated by the lecturerâs activities that should be able to motivate students to learn actively and creatively. The result showed that there was improvement in all aspects of learning so that the average score also increased from 76.18 to 84.64. It also showed that all aspects of studentsâ activities in the classroom increased, especially in the aspects of teamwork and discussion because of the number of members in each group in the 2nd cycle was relatively smaller than the number of members in each group in the 1st cycle. The quality of student learning outcomes is the output of the learning process in class. In the 2006 curriculum, student learning outcomes are based on the degree of studentsâ mastery with value standard indicator determined. The result showed that there was an increase in the studentsâ score. The highest score was from 87 to 95 and the lowest score was from 50 to 62, so the average score was 76 and the degree of mastery became 83%. It meant that students could improve their understanding of the materials and concept of risk management through the Discovery Learning approach.